Sexually dimorphic neuroimmune response to chronic opioid treatment and withdrawal. (15th March 2021) - Kumar, Mohit; Rainville, Jennifer R.; Williams, Kori; Lile, Joshua A.; Hodes, Georgia E.; Vassoler, Fair M.; Turner, Jill R.
Abstract: Opioid use disorder is a leading cause of morbidity and mortality in the United States. Increasing pre-clinical and clinical evidence demonstrates sex differences in opioid use and dependence. However, the underlying molecular mechanisms contributing to these effects, including neuroinflammation, are still obscure. Therefore, in this study, we investigated the effect of oxycodone exposure and withdrawal on sex- and region-specific neuroimmune response. Real-time PCR and multiplex cytokine array analysis demonstrated elevated neuroinflammation with increased pro-inflammatory cytokine levels, and aberrant oligodendroglial response in reward neurocircuitry, following withdrawal from chronic oxycodone treatment. Chronic oxycodone and withdrawal treated male mice had lower mRNA expression of TMEM119 along with elevated protein levels of pro-inflammatory cytokines/chemokines and growth factors (IL-1β, IL-2, IL-7, IL-9, IL-12, IL-15, IL17, M-CSF, VEGF) in the prefrontal cortex (PFC) as compared to their female counterparts. In contrast, reduced levels of pro-inflammatory cytokines/chemokines (IL-1β, IL-6, IL-9, IL-12, CCL11) was observed in the nucleus accumbens (NAc) of oxycodone and withdrawal-treated males as compared to female mice. No treatment specific effects were observed on the mRNA expression of putative microglial activation markers (Iba1, CD68), but an overall sex specific decrease in the mRNA expression of Iba1 and CD68 was found in the PFC and NAc of male mice as compared to females. Moreover, a sex and region-specific increase in the mRNA levels of oligodendrocyte lineage markers (NG2, Sox10) was also observed in oxycodone and withdrawal treated animals. These findings may open a new avenue for the development of sex-specific precision therapeutics for opioid dependence by targeting region-specific neuroimmune signaling. Graphical abstract: Image 1 Highlights: Withdrawal from chronic opioid exposure induce sex-specific pro-inflammatory neuroimmune response in reward neurocircuitry. Chronic opioid exposure and withdrawal induce sex-specific oligodendroglia alterations in reward neurocircuitry. Altered neuroimmune signaling may be associated with sexually dimorphic response in the development of opioid use disorder. Sex-specific neuroimmune modulators may be novel therapeutics for opioid use disorder.